The Effect of Branch Offices, ATMs, TPF, and Financing on Sharia Banking Market Share in Indonesia 2016-2020 - Mahendra, Taufik; Putri, Syah (Universitas Muhammadiyah Yogyakarta, 2022)
Islamic Bank is a bank that conducts activities based on the principles of Islamic law. The operational activities of Islamic banks in Indonesia were started in 1992 by PT Bank Muamalat Indonesia. And after that, Islamic banking continued to experience growth. With the growth of the Islamic banking company, the market share or market share of Islamic banking has also increased. This study aims to explain the effect of branch offices, ATMs, TPF, and financing on the market share of Islamic banking in Indonesia. This type of research is quantitative descriptive research with data obtained from secondary sources. Sampling was done by the purposive sampling technique. This type of research data is time-series statistical data on Islamic banking in Indonesia from 2016 until 2020. The method of analysis used is a linear regression of Ordinary Least Square (OLS) with the help of the Eviews 12 SV application. The results of data processing indicate that partially, branch offices, ATMs, and TPF have a significant effect on the market share of Islamic banking in Indonesia in 2016-2020. Meanwhile, financing has no significant effect on the market share of Islamic banking in Indonesia in 2015-2020. And simultaneously or simultaneously, branch offices, ATMs, deposits, and financing affect the market share of Islamic banking in Indonesia.